TaMIR1119, a miRNA family member of wheat (Triticum aestivum), is essential in the regulation of plant drought tolerance - Gui-qing SHI; Jing-ying FU; Ling-jie RONG; Pei-yue ZHANG; Cheng-jin GUO; Kai XIAO (Journal of Integrative Agriculture)
Through regulating target genes via the mechanisms of posttranscriptional cleavage or translational repression, plant miRNAs involve diverse biological processes associating with plant growth, development, and abiotic stress responses. In this study, we functionally characterized TaMIR1119, a miRNA family member of wheat (Triticum aestivum), in regulating the drought adaptive response of plants. TaMIR1119 putatively targets six genes categorized into the functional classes of transcriptional regulation, RNA and biochemical metabolism, trafficking, and oxidative stress defense. Upon simulated drought stress, the TaMIR1119 transcripts abundance in roots was drastically altered, showing to be upregulated gradually within a 48-h drought regime and that the drought-induced transcripts were gradually restored along with a 48-h recovery treatment. In contrast, most miRNA target genes displayed reverse expression patterns to TaMIR1119, exhibiting a downregulated expression pattern upon drought and whose reduced transcripts were re-elevated along with a normal recovery treatment. These expression analysis results indicated that TaMIR1119 responds to drought and regulates the target genes mainly through a cleavage mechanism. Under drought stress, the tobacco lines with TaMIR1119 overexpression behaved improved phenotypes, showing increased plant biomass, photosynthetic parameters, osmolyte accumulation, and enhanced antioxidant enzyme (AE) activities relative to wild type. Three AE genes, NtFeSOD, NtCAT1;3, and NtSOD2;1, encoding superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD) proteins, respectively, showed upregulated expression in TaMIR1119 overexpression lines, suggesting that they are involved in the regulation of AE activities and contribution to the improved cellular reactive oxygen species (ROS) homeostasis in drought-challenged transgenic lines. Our results indicate that TaMIR1119 plays critical roles in regulating plant drought tolerance through transcriptionally regulating the target genes that modulate osmolyte accumulation, photosynthetic function, and improve cellular ROS homeostasis of plants.